Journalist as Professional versus Employee - A Case of Daily Koran Sindo in Censoring News on Trump’s Travel-Ban Policy - Tjipta Lesmana (Ikatan Sarjana Komunikasi Indonesia, 2017)
Freedom of the press worldwide faces serious threat from owners of the media. Theoretically, journalist is independent and able to write whatever he or she wants to print. News is anything that fits to print, the jargon out cried in early years of Libertarian Media Theory. It is the journalist who has the power to give criteria for “fitting” to print. Now the jargon has changed drastically: “He who pays the piper calls the tune’’. Newsroom is nowadays not beyond owner’s intervention. Owners run news media for specific reason. If they decide that a commentary or a news report goes against their beliefs or their interests or if they consider them biased, they certainly will want to intervene. The case of daily Koran Sindo is interesting to be investigated. While most media in the world, including those in Indonesia, heavily exposed President Donald Trump’s controversial policy in banning people from seven middle-east and African countries from entering the US, daily Koran Sindo totally blocked the news. Not any single news criticizing Trump’s policy is printed at the paper owned by Hary Tanoesudibjo. How the daily “plays the game” the author makes a simple research using qualitative content analysis. .